Laparoscopic Appendectomy Trends and Outcomes in the United States: Data from the Nationwide Inpatient Sample (NIS), 2004–2011. Issue 10 (October 2014) - Masoomi, Hossein; Nguyen, Ninh T.; Dolich, Matthew O.; Mills, Steven; Carmichael, Joseph C.; Stamos, Michael J.
Laparoscopic appendectomy (LA) is becoming the standard procedure of choice for appendicitis. We aimed to evaluate the frequency and trends of LA for acute appendicitis in the United States and to compare outcomes of LA with open appendectomy (OA). Using the Nationwide Inpatient Sample database, we examined patients who underwent appendectomy for acute appendicitis from 2004 to 2011. A total of 2, 593, 786 patients underwent appendectomy during this period. Overall, the rate of LA was 60.5 per cent (children: 58.1%; adults: 63%; elderly: 48.7%). LA rate significantly increased from 43.3 per cent in 2004 to 75 per cent in 2011. LA use increased 66 per cent in nonperforated appendicitis versus 100 per cent increase in LA use for perforated appendicitis. The LA rate increased in all age groups. The increased LA use was more significant in male patients (84%) compared with female patients (62%). The overall conversion rate of LA to OA was 6.3 per cent. Compared with OA, LA had a significantly lower complication rate, a lower mortality rate, a shorter mean hospital stay, and lower mean total hospital charges in both nonperforated and perforated appendices. LA has become an established procedure for appendectomy in nonperforated and perforated appendicitis in all rates exceeding OA. Conversion rate is relatively low (6.3%).